A retrospective survey evaluating the prescribing tendencies of UK veterinary surgeons, relating to the use of anti-inflammatory drugs in canine angiostrongylosis. (2nd July 2021) - Loverance, Amy; Wright, Ian; Dunning, Mark; Elsheikha, Hany
Abstract : Background: In addition to anti-parasitic therapy, appropriate supportive care is vital for the successful treatment of canine angiostrongylosis. Aim: This study sought to determine the prevalence and reasons for the use of corticosteroids and non-steroidal anti-inflammatory drugs, by veterinarians, as a supportive treatment for canine angiostrongylosis. Specifically, the study investigated the use of anti-inflammatory drugs in the management of inflammation, anaphylaxis and immune-mediated thrombocytopenia, which can develop in some dogs infected by Angiostrongylus vasorum . Methods: These aims were achieved by surveying UK veterinarians from a non-endemic area, Yorkshire, and an endemic area, South East England, for canine angiostrongylosis. Responses were received from independent, corporate-owned and referral practices. Results: Overall, more veterinarians would administer corticosteroids (80%) compared with non-steroidal anti-inflammatories (40%). Most respondents surveyed stated administration would be case dependent, including the severity of perceived inflammation. Four of six veterinarians who would never administer non-steroidal anti-inflammatories cited coagulopathies as the reason for their decision-making. While the regional comparison here revealed no significant differences, wider sampling may produce identifiable trends. Conclusion: The survey responses revealed a lack of understanding of if, when, and why, anti-inflammatories should be administered. Imperatively, further research is needed to address this lacuna.